A surface science view onto cuprous oxide: Growth, termination, electronic structure and optical response - Nilius, Niklas; Goniakowski, Jacek; Noguera, Claudine (Surface science reports, 2024)
The oxides of copper have attracted the attention of scientists already for more than hundred years. This fascination is fueled by many outstanding properties of the material, for example, a semiconducting behavior that led to the first diode fabricated in electronics, a pronounced excitonic response that stimulated an intense search for Bose-Einstein condensation, and a pivotal role in unconventional superconductivity. Despite this central position in past and present research activities, many aspects of copper oxides are not sufficiently understood to date. This applies in particular to their surface characteristics, where even fundamental questions, such as the energetically favored termination of low-index Cu2O and CuO planes, are still subject of debates. This review aims at addressing these deficiencies by compiling state-of-the-art knowledge of the surface science of copper oxides, and especially of cuprous oxide. A first focus of the article lies in the oxidation characteristic of copper as a means to prepare well-defined oxide surfaces. It demonstrates that low-pressure oxidation only results in the formation of ultrathin precursor oxides, with properties deviating substantially from those of the bulk material. Consequently, reliable pathways to produce high-quality and bulk-compatible surfaces, either of Cu2O thin films or bulk crystals, are presented. The following chapter provides a comprehensive introduction into the atomic structure of the most relevant Cu2O surfaces, i.e., the (111), (100) and (110) planes. It gives an overview of important diffraction and microscopy experiments on the most accessible Cu2O terminations, and complements this with state-of-the-art theoretical studies to develop corresponding atomistic models. The chapter closes by presenting the atomic configurations of the most relevant Cu2O surfaces at given thermodynamic conditions. Chapter four develops a surface-science view onto the unique optical response of cuprous oxide. After introducing the well-known bulk behavior, it highlights how optical properties can be probed on surfaces with high spectral and spatial resolution. The chapter discusses how optical near-field techniques are employed to analyze oxide excitons and their trapping at lattice defects in real-space experiments. The last chapter summarizes efforts to alter intrinsic Cu2O properties, e.g., the p-type conductivity, the width of the band gap and the exciton trapping and recombination behavior, via doping. It illuminates this topic from an experimental and theoretical viewpoint and highlights several unsolved questions related to the topic. Despite considerable efforts, this review can only present the current state of knowledge on Cu2O surfaces, a subject that continuously advances due to new scientific findings and innovations. We nonetheless hope that it provides a comprehensive and topical overview of the unusual properties of this fascinating oxide system.